Offerings and User Demands of eHealth Services in Spain: National Survey - Andrés Cernadas Ramos; Ángela Fernández Da Silva; Bran Barral Buceta; Ramón Bouzas-Lorenzo (JMIR Publications, 2023)
BackgroundThe accelerated development of information and communication technologies has made health care one of the pioneering fields in the incorporation of these tools. As new technologies have been applied, existing technologies have been sophisticated and improved and the concept of eHealth has expanded. However, these advances and expansion of eHealth do not seem to have served to adapt the supply of services to users' demands; rather, supply seems to be governed by other variables. ObjectiveThe main objective of this work was to review the existing differences between user demands and the supply of eHealth services in Spain and their causes. The aim is to provide information on the level of use of the services and the causes of the variation in demand for these services, which can be useful in correcting existing differences and adapting them to the needs of users. MethodsA survey, "Use and Attitudes Toward eHealth in Spain," was applied by telephone to a sample of 1695 people aged 18 years and over, taking into account sociodemographic profile characteristics (sex, age, habitat, educational level). The confidence level was set at 95% and the margin of error was ±2.45 for the whole sample. ResultsThe survey results showed that the online doctor's appointment service is the most frequently used eHealth service by users: 72.48% of respondents used this service at some point and 21.28% stated that they use it regularly. The other services showed significantly lower percentages of use, including "managing health cards" (28.04%), "consulting medical history" (20.37%), "managing test results" (20.22%), "communicating with health professionals" (17.80%), and "requesting a change of doctor" (13.76%). Despite this low usage, a large majority of respondents (80.00%) attach great importance to all the services offered. Overall, 16.52% of the users surveyed were willing to make new service requests to the regional websites, with 9.33% of them highlighting services such as "the availability of a complaints and claims mailbox," "the possibility of consulting medical records," and "the availability of more detailed information on medical centers (location, medical directory, waiting lists, etc)." Other outstanding requests (8.00%) were to simplify the procedures for using certain existing services. ConclusionsThe data from the survey show that eHealth services are widely known and highly valued by users, but not all services are used with the same frequency or intensity. It appears that users find it difficult to suggest new services that might be useful to them in terms of demand for new services that do not currently exist. It would be useful to use qualitative studies to gain a deeper understanding of currently unmet needs and the possibilities of eHealth. The lack of access to and use of these services and the unmet needs particularly affect more vulnerable populations who have the greatest difficulty in meeting their needs through alternative means to eHealth.